2013 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--22396
|View full text |Cite
|
Sign up to set email alerts
|

Purdue University’s Engineering Leadership Program: Addressing the Shortfall of Engineering Leadership Education

Abstract: Teaching interests relate to the professional development of graduate engineering students and to leadership, policy, and change in science, technology, engineering, and mathematics education. Primary research projects explore the preparation of engineering doctoral students for careers in academia and industry and the development of engineering education assessment tools. She is a National Science Foundation Faculty Early Career (CA-REER) award winner and is a recipient of a Presidential Early Career Award fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Leadership education should be implemented early on in an academic career -Early implementation gives more time for students to develop the leadership skills desired. Because the skills sometimes take time to instil, the more time that is given the better 8,15 .…”
Section: The Need For Experiential Leadership Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…Leadership education should be implemented early on in an academic career -Early implementation gives more time for students to develop the leadership skills desired. Because the skills sometimes take time to instil, the more time that is given the better 8,15 .…”
Section: The Need For Experiential Leadership Educationmentioning
confidence: 99%
“…Active involvement of students allows them to take responsibility for their own learning and the learning of others -It has been shown that when students are in charge of their own learning and the learning of others that they learn more. In addition, allowing students to be in charge of their own learning prepares them for a life of learning 12,15,20 .…”
Section: The Need For Experiential Leadership Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…al. [18] and Albdeli [19] conferred that learning through experiential model involved lots of time. Hence its applicability in technical curriculum is less flexible.…”
Section: Literature Surveymentioning
confidence: 99%